Antiinflammatory Effect of Several Umbelliferae Species - SUWIJIYO PRAMONO (Bogor Agricultural University, Indonesia, 2005)
A screening for antiinflammatory effects was performed on several Indonesian Umbelliferae plants based on the contents of saponins and flavonoids. They were compared with Bupleurum falcatum L. as an introduced antiinflammatory plant. Roots and grains of each plant were collected, dried, and extracted with ethanol. The ethanolic extracts were then analyzed for their saponin and flavonoid contents by gravimetric and UV-vis spectrophotometric method. Antiinflammatory activity test was conducted on carragenin induced rat paw oedema. The results showed that the highest contents of saponin and flavonoid were found in the grains of Apium graveolens L. and showed antiinflammatory effect that was equivalent to that of the root of B. falcatum.